2016
DOI: 10.1016/j.neuroimage.2015.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Radial bias is not necessary for orientation decoding

Abstract: Multivariate pattern analysis can be used to decode the orientation of a viewed grating from fMRI signals in early visual areas. Although some studies have reported identifying multiple sources of the orientation information that make decoding possible, a recent study argued that orientation decoding is only possible because of a single source: a coarse-scale retinotopically organized preference for radial orientations. Here we aim to resolve these discrepant findings. We show that there were subtle, but criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…The source of the information used to decode orientation with MRI or MEG measures has provoked lively debate (Kamitani and Tong, 2005;Pratte et al, 2016;Swisher et al, 2010;summarised by Maloney, 2015). It has been suggested that decoding performance could be due to coarse-scale effects such as radial biases (Mannion et al, 2010), edge effects (Carlson, 2014), or differential allocation of attention .…”
Section: Discussionmentioning
confidence: 99%
“…The source of the information used to decode orientation with MRI or MEG measures has provoked lively debate (Kamitani and Tong, 2005;Pratte et al, 2016;Swisher et al, 2010;summarised by Maloney, 2015). It has been suggested that decoding performance could be due to coarse-scale effects such as radial biases (Mannion et al, 2010), edge effects (Carlson, 2014), or differential allocation of attention .…”
Section: Discussionmentioning
confidence: 99%
“…Encoding of spatial position is spatially smooth in V1, with the scale of retinotopic maps being similar to the voxel sizes typically used in neuroimaging, whereas encoding of orientation is much more spatially fine-grained (see Issa et al, 2008;Ng et al, 2007). Indeed, orientation maps are so fine-grained compared to the spatial scale of voxels in typical experiments that researchers have debated for years how it is that we are able to decode orientation from V1 using fMRI in the first place (e.g., Alink et al, 2013;Pratte et al, 2016;Maloney, 2014).…”
Section: Simulation 2: False Positive Invariance Can Results From Homomentioning
confidence: 99%
“…Subjects viewed the screen via an angled mirror attached to the head coil. Visual stimuli were full-contrast square-wave gratings with a spatial frequency of 1.5 cycles per degree of visual angle (similar to Alink et al, 2013;Pratte et al, 2016;Sengupta et al, 2017), a frequency known to drive V1 responses strongly (Henriksson et al, 2008), shown through a wedge-shaped aperture window that spanned from 1.5°to 10°of eccentricity and 100°of polar angle ( Figure 2). The aperture window had four possible locations, starting at 20°, 80°, 200°, and 260°of rotation.…”
Section: Stimulimentioning
confidence: 99%
“…Yet, if changes occur at the level of individual voxels, they 696 may be driven by neuronal modulations at the level of columnar-scale tuning maps: 697 for example, it has been hypothesised that the ability to decode local radial biases 698 from primary visual cortex is driven by selective activation of orientation-selective 699 neurons within the orientation pinwheels (Mannion et al, 2009). Additionally, recent 700 work has provided evidence for the complexity of voxel tuning profiles within the 701 early visual cortex and demonstrated that experimental task design can influence the 702 conclusion that radial bias is the only source of orientation information within fMRI 703 signals, for example (Pratte et al, 2016). Hence, global areal maps are unlikely to 704 fully account for the ability to decode orientation signals within early visual cortex 705 (e.g.…”
Section: Discussionmentioning
confidence: 99%